ANALISIS PENGARUH SUMBER-SUMBER PENDAPATAN ASLI DAERAH (PAD) TERHADAP ALOKASI BELANJA DAERAH PADA KABUPATEN TOJO UNA-UNA - Badjulu, Ramlianty (Katalogis, 2014)
The objectives of the study are: (1). To determine and analyze development of local revenue consisting of local taxes and local retribution in Tojo Una-una Regency, (2). To determine and analyze simultaneous impact local taxes and local retributions on regional spending allocation in Tojo Una-una Regency, (3). To determine and analize partial impact of local taxes on regional spending allocation in Tojo Una-una Regency, (4). To determine and analyze simultaneous impact of local retributions on regional spending allocation in Tojo Una-una Regency. Based on the result of multiple regression testing, it is found R2 = 0.322 or 32,2 %, it mean that independent variables namely local taxes and local retribution can explain the variation or have an influence on regional spending allocation at 32,2%, while the remaining 67,8 % is explained or influenced by other variables outside the model. Local taxes and local retributions have simultaneous and significant effect on regional spending allocation in Tojo Una-una Regency. Local taxes have significant effect on regional spending allocation spending allocation in Tojo Una-una Regency.